(untitled) (Alternautas, 2023)
Since Dina Boluarte took Peru’s presidency, the Police repression and military violence caused more than 60 deaths. Massive mobilizations reject her, promoting journeys from the Andes to Lima. These urgent claims are echoed by civil groups, among which “Retablos por la Memoria” stands out, appropriating a rural traditional artistic expression to denounce and mourn the assassinated. Initiated by feminist artists, they have spread in Peruvian cities and abroad, creating bridges in a fragmented and depoliticized society. In a country still affected by the internal armed conflict (80s-2000s) and harshly beaten by Covid-19, “Retablos por la Memoria” contests impunity while demanding radical change: a regenerative form of artivism in an extremely violent battleground.